2017
DOI: 10.25103/jestr.106.25
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Pile Response Subjected to Different Combination of Loadings

Abstract: Pile-soil interaction has been a subject of interest to many earlier researchers. However, not much work has been done on the effects of structural response of single piles subjected to different combination of axial and lateral loads and hence the respective pile-soil interaction. The main objectives of this paper are to assess the influence of axial load intensities on the lateral single isolated pile response in various pile slenderness ratios. Three-dimensional finite element approach was used to simulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Finite element analyses was further extended to study the lateral response of pile embedded in both cohesive and cohesionless soil and subjected to different combination of vertical and lateral loads, It was confirmed that the presence of the vertical load and its intensity affects the lateral behavior of single pile [11].…”
Section: Introductionmentioning
confidence: 88%
“…Finite element analyses was further extended to study the lateral response of pile embedded in both cohesive and cohesionless soil and subjected to different combination of vertical and lateral loads, It was confirmed that the presence of the vertical load and its intensity affects the lateral behavior of single pile [11].…”
Section: Introductionmentioning
confidence: 88%
“…According to the authors, these limited studies were not covered most of the pile foundation conditions that usually influence on the lateral pile performance under such loading condition, such as pile cross section, pile slenderness ratio, and soil density, especially by using laboratory program. The number of limited studies, including the pile performance under combined loading such as Karthigeyan et al 2006&2007, Rajagopal and Karthigeyan 2008, Abbas et al 2010, 2015and 2017 In the present study, the effect of pile cross sections on the behavior of it under combined loads was investigated with into consideration some parameters like: the values of combined load, the slenderness ratios of the pile, and pile materials.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations have attempted to study the lateral response of pile under pure lateral load using the finite element approach [9,11,16,23,24]. In addition, the influence the lateral pile response in 3D finite element approach when the pile carried both axial and lateral loads was studied by [12,13] and [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…2006, Kahyaoglu 2009 and Taha 2018). In addition, the influence the lateral pile response in 3D finite element approach when the pile carried both axial and lateral loads was studied by Karthigeyan et al (2006Karthigeyan et al ( & 2007 and Abbas et al (2015 and2017). Therefore, in this study, the importance of conducting a fundamental study is discussed.…”
mentioning
confidence: 99%